Morphofunctional features of endometrium in women with combination of male and female factors - Nosenko, O. M.; Seylova, A. I. (Journal of Education, Health and Sport, 2019)
Treatment couples with a combination of male and female factor infertility is the most difficult and often requires precisely ART. However, ICSI efficacy currently does not exceed 35-40 %, about a third of all pregnancies are terminated early. The purpose of the study was to determine the morphofunctional features of endometrium in women from married couples with a combination of female and male factors of infertility. Material and methods. There were 100 married couples with prospective follow-up with a combination of male and female infertility factors of group A who had applied for assisted reproductive technologies (ART). All men in group A suffered from pathozoospermia. Control group C consisted of 34 couples with secondary infertility of tube genesis, who consisted of conditionally somatically healthy women with a history of childbirth, without fallopian tubes, and their men with normozoospermia. Group A was stratified each into 3 subgroups. The A1 subgroup (n = 32) included married couples who had chronic anovulation; in subgroup A2 (n = 37) - married couples who had tubal infertility; in subgroup A3 (n = 31) - married couples in which women had a combination of tubal and anovulatory factors of infertility. Material for morphological examination were endometrial pipel-biopsy specimens on day 21-22th of the menstrual cycle on the day of the expected implantation window. It were determined expression of HOXA10, Leukemia inhibitory factor (LIF), glycoprotein 130 (gp130), interleukin-6 (IL-6) in endometrium. Results: morphofunctional status of women’s endometrium with a combination of female and male infertility factors was characterized by an increase in estrogen-α receptor IRS in the glands and endometrial stroma, respectively, 1.86 (p <0.01) and 1.37 (p<0.01) times, respectively. expression of P4 receptors in endometrial glands 1.48 times (p<0.01) against the background of their decrease in stroma by 1.39 (p<0.01); increase in infiltration of endometrial stromal CD56+ - positive natural killer cells by 10.22 times (p<0.01) and presence of CD138+ immunopositive cell cells in 66.00 % of cases. Patients with a combination of male and female infertility factors have individual changes in endometrial morphofunctional features during the intended implantation window, one only that should be considered when determining the tactics of treating women with different male forms. Conclusions. Changes in the proteomic profile of the endometrium play an important role in the occurrence of reproductive disorders and are individual depending on the combination of various of female and male factors of infertility.